The Use of Zakat Proceed for Takaful Protection of Aṣnaf (Qualified Receivers): A Maqasid-Base Ijtihad Perspective in Malaysia - Muhammad Najib Abdullah; Syaryanti Hussin; Arishah Abdul Anis (Faculty of Syariah and Law, Universiti Sains Islam Malaysia, 2026)
International Conference of Postgraduate Students and Academics in Syariah and Law 2025 (INPAC 2025) “Advancing Malaysia Madani through Global Shariah and Legal Research.” Organized by the Faculty of Syariah and Law, Universiti Sains Islam Malaysia (USIM)